EFEKTIVITAS PEMANFAATAN DANA DESA (DD) UNTUK KESEJAHTERAAN MASYARAKAT DESA - Sasmita, Andin (Journal of Development Economic and Social Studies, 2022)
The effectiveness of village fund usage in village development and community empowerment is a benchmark for assessing the success of the usage, which is proven by effective and on-target village development and community empowerment activities. The number of underprivileged households in Balongpacul village is increasing in every year. Therefore, the effectiveness of village fund usage is emphasized to increase public welfare. This qualitative descriptive study was conducted in the said village . the primary data was obtained through interviews with suitable informants, while the secondary was gathered from documents related to the research topic. The entire data was then analyzed through data reduction, presentation, and conclusion drawing. This study finds that the effectiveness of the village funds usage can be seen from the Minister of Village’s regulation, Municipal Government’s regulation, and from the fact on the field. The fund was prioritized for village development and community empowerment. Therefore, it can be concluded that the effectiveness of the village fund usage has been in conformance with both regulations as well as with the fact on the field. In addition, the use of the village fund gives a positive impact to the society.